ASSESSMENT OF QUALITY STABILITY OF COMPOSITE FLOURS PRODUCED BY DAR ES SALAAM SMES - Rweyemamu, Leonard M. P (Tanzania Journal of Engineering and Technology, 2017)
A study was conducted to assess quality stability of cereal flours processed by food processing SMEs in Dar es Salaam. This product is obtained by mixing various cereal grains and is considered as of higher nutritional values in Tanzania. The shelf-life was predicted by determining water activity (a w ) and moisture content (MC) levels and plotting the water sorption isotherms (MSI). Ninety per cent of investigated samples (N=78) were found packaged in the materials of various quality conditions. It was found that the packaging materials mostly used is plastic films (63%), paper packets/bags (26%), hard papers (3%), plastic jars (1%) and combination of paper packets/boards inserted with plastic film (7%). Water sorption isotherms were plotted for single and multiple ingredient products. The highest levels of a w were observed for products in paper bags with 0.63 (a w ) and 0.13 MC (kg water/kg solids). Plastic films and jars had intermediate levels at 0.52 (a w ) and 0.042 MC (kg water/kg solids), and combined paper packets/boards with plastic films had lowest levels at 0.43 (a w ) and 0.038 MC (kg water/kg solids) exhibiting highest stability of products packaged in these materials. Relative humidity and temperature at sampling locations ranged from 80 to 94% and 30 to 34oC, respectively. Multiple ingredient products showed the lowest a w and MC levels, whereas single ingredient flours possessed higher a w and MC values. Generally, the package system comprising paper board (or hard paper/box) and plastic bag (plastic film) was the most stable followed by plastic films, and paper bag by far.